Crystallization of hydrogenated sunflower-cottonseed oil - Rivarola, G. (1987)
Crystal structures formed during solidification of hydrogenated cottonseed oil, sunflowerseed oil and their blends were analyzed by using an X-ray diffraction technique, differential scanning calorimetry (DSC) and polarized light microscopy. Temperatures and times of crystallization under conditions which tend to produce β′ type structures were determined in terms of refrigeration parameters. Microscopy with polarized light also helped clarify some aspects of the tridimensional network of crystals that contribute to the consistency of products made from hydrogenated oils.